2018
DOI: 10.1016/j.ajoc.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset bleb-associated endophthalmitis and continuous positive airway pressure

Abstract: PurposeTo raise awareness of a possible association between continuous positive airway pressure (CPAP) devices and postoperative bleb-related infection.ObservationsA 57-year old patient on CPAP presented with unilateral bleb-associated endophthalmitis 32 months after routine ExPress Trabeculectomy with mitomycin C. The offending organism, Streptococcus mitis, is a nonmotile and generally non-virulent pathogen which predominates in the normal human respiratory flora.Conclusions and importanceThis conceptual rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In a case study, effect of CPAP in a 57-year-old patient's eye presented with unilateral bleb-associated endophthalmitis. 75 In another case, corneal neovascularization with associated lipid keratopathy was reported in a patient with OSA using CPAP. 76 Air leakage from the n-CPAP mask towards the left globe was reported by the patient which may have been the cause of this complication.…”
Section: Ocular Complicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…In a case study, effect of CPAP in a 57-year-old patient's eye presented with unilateral bleb-associated endophthalmitis. 75 In another case, corneal neovascularization with associated lipid keratopathy was reported in a patient with OSA using CPAP. 76 Air leakage from the n-CPAP mask towards the left globe was reported by the patient which may have been the cause of this complication.…”
Section: Ocular Complicationsmentioning
confidence: 95%
“…Although both eyes showed similar measurements before CPAP therapy, these parameters changed significantly after CPAP use. In a case study, effect of CPAP in a 57‐year‐old patient's eye presented with unilateral bleb‐associated endophthalmitis . In another case, corneal neovascularization with associated lipid keratopathy was reported in a patient with OSA using CPAP .…”
Section: Pressure‐related Side Effectsmentioning
confidence: 99%
“…There was even one report of a trabeculectomy blebrelated endophthalmitis, which the authors believed to have been caused by a spread of bacteria from the respiratory tract to the eye via the CPAP mask. 117 A more systematic study found that about one-fifth of CPAP therapy users had previous episodes of conjunctivitis secondary to CPAP mask leaks. 28 However, on average, there were no significant difference in rates of ocular irritation symptoms between CPAP and non-CPAP users, and CPAP users even had longer tear break-up time than non-users.…”
Section: Ocular Surface Complications Related To Cpap Therapy Usementioning
confidence: 99%
“…Streptococcus mitis presents with a moderate frequency concerning BRIs and we have reported 17 culture-proven cases. Among them, a late-onset BRE attributed to Streptococcus mitis, which possibly translocated from respiratory flora due to continuous positive airway pressure (CPAP), was described by Berg et al [ 67 ]. Furthermore, skin flora microorganisms of low virulence, such as Dermabacter hominis and Kocuria rosea, have also been identified in BRE cases [ 6 ].…”
Section: Pathogensmentioning
confidence: 99%